Grounding Aswaja: Efforts to Stem the Movement of Religious Radicalism in Nurul Islam Jember Boarding School - Miftahus Sa'diyah; Maslathif Dwi Purnomo (LP2M UIN Kiai Haji Achmad Siddiq Jember, 2023)
Ahlussunnah wal jama'ah itself is a teaching that adheres to the five sources of law. The five sources of law are the Qur'an, Hadith, Fiqh, Ijma', Qiyas. And Indonesia is a country with the largest Muslim population in the world, with the majority adhering to the teachings of ahlussunnah wal jama'ah (aswaja). This article reviews the efforts made by Educational Institutions to ground Aswaja's identity. In particular, the cultivation of the Aswaja identity was carried out to ward off the Transnational Islamic movement which is currently rife among teenagers, especially in educational institutions. This article examines the implementation of Aswaja learning material at Islamic Junior High School Nurul Islam. This implementation is an effort to strengthen the understanding of Wasatiyah Islam among students so that it is not easy to get caught up in radical takfiri teachings. This study uses field research (field research) with qualitative methods. The approach used in this research is a descriptive research approach. The results of the study showed that the implementation of the Aswaja material at Islamic Junior High School was carried out through three stages including planning, review, evaluation, and outreach to student guardians. In addition, the application of this Aswaja material contributes to increasing students' understanding of Wasatiyah Islam including its history, religious beliefs adopted, its amaliyah teachings, as well as other understandings that conflict with Aswaja or Wasatiyah Islam.